2020
DOI: 10.1101/2020.05.21.102350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat Shock Protein 27 Immune Complex Upregulates LDLR Expression Thereby Reducing Plasma Cholesterol and Atherogenesis

Abstract: 1Elevated Heat Shock Protein 27 levels predict relative freedom from cardiovascular events. In 2 ApoE -/mice HSP27 over-expression or twice daily subcutaneous injections reduce blood and 3 plaque cholesterol levels, inflammation and atherogenesis. While natural antibodies to HSP27 4 are present in human blood their role is unknown. Here, we show that blood levels of both 5 HSP27 and anti-HSP27 IgG antibodies are elevated in healthy controls compared to patients with 6 cardiovascular disease. ApoE -/mice vaccin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Heat shock protein 27 (HSP27) is a member of the small HSP protein family and is involved in a variety of biological activities including ATP-independent molecular chaperoning, prevention of apoptosis, and more recently attenuating atherogenesis. Our laboratory reported that reduced serum HSP27 levels are associated with cardiovascular disease [17,18], and along with four independent laboratories demonstrated reduced arterial HSP27 expression with atherosclerosis [19][20][21][22]. Conversely, we showed that increasing HSP27 serum levels, by systemic over-expression, bone marrow transplantation or administration of the recombinant protein, not only reduced plaque burden, but also correlated with a lower tendency for experimental plaque rupture [23,24].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Heat shock protein 27 (HSP27) is a member of the small HSP protein family and is involved in a variety of biological activities including ATP-independent molecular chaperoning, prevention of apoptosis, and more recently attenuating atherogenesis. Our laboratory reported that reduced serum HSP27 levels are associated with cardiovascular disease [17,18], and along with four independent laboratories demonstrated reduced arterial HSP27 expression with atherosclerosis [19][20][21][22]. Conversely, we showed that increasing HSP27 serum levels, by systemic over-expression, bone marrow transplantation or administration of the recombinant protein, not only reduced plaque burden, but also correlated with a lower tendency for experimental plaque rupture [23,24].…”
Section: Introductionsupporting
confidence: 52%
“…To study the in vitro role of exosomal HSP27 we will incorporate new information showing that anti-HSP27 IgG antibodies levels are more abundant in healthy subjects vs. CVD patients. To this end, we have generated and validated a polyclonal anti-HSP27 IgG antibody (PAb) that combines with HSP27 to form an immune complex (IC) that facilitates the biological effects of HSP27 (referred to as Immune Complex Altered Signaling and Transport (ICAST)) [18,26].…”
Section: Introductionmentioning
confidence: 99%
“…We used a validated rabbit anti-HSP27 polyclonal antibody (PAb) that shares the same epitope mapping pattern as human plasma-derived AAbs. 11 Herein, we show that compared to HSP27 alone, the HSP27 IC shows enhanced cell membrane interactions that result in altered signaling with key receptors involved in inflammation (Toll Like Receptor 4; TLR4) and oxLDL uptake (scavenger receptors, SR-AI and CD-36). Manassas, VA) and incubated at 37°C and 5% CO 2 in complete RPMI 1640 growth medium supplemented with 10 U/mL of penicillin and streptomycin, 1 mM of sodium pyruvate (11965092; Thermo Fisher Scientific, Burlington, ON) and heat inactivated 10% Fetal Bovine Serum (FBS; Gibco, Burlington, ON).…”
Section: Introductionmentioning
confidence: 86%
“…The production and validation of this PAb is previously described. 11 To verify the fidelity of this PAb, we compared its immunoreactivity with a commercial (goat) anti-HSP27 antibody using Western blotting of rHSP27 and rHSP25. As well, we used a spot blot epitope mapping technique to compare the immunoreactivity of the PAb vs naturally occurring anti-HSP27 antibodies found in human plasma.…”
Section: Generation and Validation Of Anti-hsp27 Igg Polyclonal Antmentioning
confidence: 99%
See 1 more Smart Citation